Glacial-interglacial dust and export production records from the Southern Indian Ocean - Thöle, Lena Mareike; Amsler, Helen Eri; Lippold, Jörg (Earth and planetary science letters, 2019)
We present 230Th-normalized dust and export production fluxes for two contrasted marine sediment cores spanning the Antarctic Polar Front, close to the Kerguelen Plateau in the Southern Indian Ocean, covering the last glacial cycle. We report glacial lithogenic fluxes comparable to the South Atlantic and higher than in the South Pacific sectors of the Southern Ocean. Structural and temporal discrepancies with dust reconstructions from Antarctic ice cores and the Atlantic and Pacific sectors of the Subantarctic Zone (SAZ) point towards Southern Africa and/or the Kerguelen Plateau as an additional source of lithogenic material to the Southern Indian Ocean during the last ice age. In the SAZ, export production proxies respond to iron (Fe) fertilization with total organic carbon (TOC) fluxes as high as those previously reported from the Atlantic sector of the Southern Ocean. However, the correlation between export production and dust proxies is weaker than in the other sectors, and shows a muted response of export production during peak glacials. We hypothesize that this muted response may be related to macronutrient (co-)limitation imposed on phytoplankton growth possibly induced by a northward displacement of wind-driven upwelling and/or the polar frontal system during peak glacials. The Antarctic Zone (AZ) record depicts the typical pattern of enhanced export production during interglacials and comparatively low productivity during glacials suggesting a decrease in the supply of macronutrients to the AZ surface during ice ages compared to warm periods, as previously proposed. However, a muted response of opal fluxes during marine isotope stage (MIS) 5e argues for a southward migration of the frontal system during warmer MIS 5e, possibly causing silicic acid (co-)limitation at this site. These results illustrate the important role of Fe fertilization and changes in wind-driven upwelling intensities in modulating the strength and efficiency of the biological carbon pump in the Southern Ocean, but also highlight the potential role of frontal movements in explaining export production variability at sites located close to the Antarctic Circumpolar Current (ACC) fronts. Overall, our new datasets provide new insights on the regional differences in dust and export production patterns that need to be considered in order to evaluate the efficiency of carbon sequestration in the different sectors of the Southern Ocean during ice ages.
Gesehen am 21.08.2019